Orthodontic, periodontal and prosthodontic treatment for a periodontally compromised patient with a deep overbite - Ouyang Wanlu; Qian Yufen (Australasian Orthodontic Journal, 2020)
Periodontitis may result in displacement, overeruption and the tilting of teeth, which can lead to occlusal prematurities and accelerate the loss of periodontal structures. Orthodontic treatment is needed to correct displaced tooth positions, but inappropriate force and tooth movement can lead to further loss of supporting tissues.